2022
DOI: 10.1155/2022/1542117
|View full text |Cite
|
Sign up to set email alerts
|

miR-1266-3p Suppresses Epithelial-Mesenchymal Transition in Colon Cancer by Targeting P4HA3

Abstract: Numerous studies have been conducted to demonstrate that miRNA is strongly related to colon cancer progression. Nevertheless, there are few studies regarding the function for miR-1266-3p in colon cancer, and the molecular mechanism remains poorly know. Our study was designed to examine the level of miR-1266-3p expression among the colon cancer tissue and cell and to study the role and regulatory mechanism for miR-1266-3p among colon cancer’s malignant biologic behavior. First, we found that miR-1266-3p express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Many previous studies have shown that P4HA3 promotes tumor cell growth, proliferation, and metastasis in HNSC by activating the EMT process ( Wang et al, 2020 ). Targeting P4HA3 inhibits EMT in colon cancer ( Zhou et al, 2022a ). TGF-β enables cancer cell invasion and metastasis and inhibits the anti-tumor activity of immune cells ( Derynck et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have shown that P4HA3 promotes tumor cell growth, proliferation, and metastasis in HNSC by activating the EMT process ( Wang et al, 2020 ). Targeting P4HA3 inhibits EMT in colon cancer ( Zhou et al, 2022a ). TGF-β enables cancer cell invasion and metastasis and inhibits the anti-tumor activity of immune cells ( Derynck et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…P4HA3 (prolyl 4-hydroxylase subunit alpha 3) is a protein-coding gene that belongs to the prolyl 4-hydroxylase family members. A study found that P4HA3 expression is upregulated in patients with renal cell carcinoma (RCC), promoting cancer growth, invasion, and metastasis ( Zhou et al, 2022a ). It has been reported that in gastric cancer (GC), P4HA3 is significantly upregulated compared to normal tissue and is associated with unfavorable overall survival (OS) ( Song et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…MiRNA is a small, non-coding, single-stranded RNA molecule consisting of about 19-23 nucleotides (37). MiRNA regulates gene expression mainly by degrading mRNA or inhibiting its translation (38).…”
Section: Organ/tissue Genesmentioning
confidence: 99%
“…Certain miRNAs bind to the 3′-UTRs of target mRNAs to inhibit gene expression [ 7 ]. For example, miR-1266-3p can inhibit the development of colon cancer by targeting the 3′-UTR of P4HA3 and inhibiting its expression [ 8 ]. Studies showed differential miRNA expression is involved in the ongoing pathophysiology of OA [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%